Does Bystander Intervention Training Work? When Employee Intentions and Organisational Barriers Collide - Kuntz, Joana C. (Journal of interpersonal violence, 2023)
Scholars have recently begun to consider the role of bystander intervention training in countering workplace incivility and bullying. Given the scarce empirical evidence of bystander training outcomes in occupational settings, this study set out to evaluate the effectiveness of a bystander intervention training in a large healthcare organisation, by assessing changes to levels of psychological safety, bystander efficacy, intent and behaviours over time. One hundred and forty employees in a large healthcare organisation in New Zealand attended the training and were asked to complete three surveys, one conducted at baseline, one carried out 2 weeks following the training and the last survey conducted 2 months later. The qualitative and qualitative findings of this study show that the bystander intervention training resulted in significant improvements to bystander attitudes and beliefs, which were ascribed to the quality of training materials, the facilitator and opportunities to role-play bystander intervention strategies. However, the positive bystander beliefs, attitudes and intent to intervene declined in the months following the training. The qualitative findings shed a light on these results and suggest that the participants required support for training transfer in the form of updated and accessible information about negative acts and bystander intervention strategies, leadership support and role modelling of bystander behaviours and civility, and the implementation of accountability systems that ensure the ongoing development of a civility culture.